PELATIHAN BAHASA PEMROGRAMAN ANDROID : - Erwin Panggabean1; Awaludin Fitra; Martua Sitorus (Aptekmas Jurnal Pengabdian pada Masyarakat, 2022)
The development of mobile or android-based technology is now very advanced and is often used for the world of information technology, business, education and learning media. Along with the fulfillment of the needs of android-based programmers in the city of Medan, it is still far from the expected amount even though the income obtained by mastering this programming is very large, as evidenced by the large number of new rich people who have succeeded through mastering this android-based mobile programming. The development of mobile or android-based technology is now very advanced and is often used for the world of information technology, business, education and learning media. Along with the fulfillment of the needs of android-based programmers in the city of Medan, it is still far from the expected amount even though the income obtained by mastering this programming is very large, as evidenced by the large number of new rich people who have succeeded through mastering this android-based mobile programming. From the results of the questionnaire, the level of understanding of participants in the use of android applications, namely 85% stated that they understood using android applications in the operation of mathematical calculations. And 15% do not understand. And from the results of the satisfaction level of participants who stated that they were very satisfied by 90% with the activities carried out. And 10% are dissatisfied with the reason the training time is too short.